2003
DOI: 10.1177/1534735403259064
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Massage and Healing Touch Improve Symptoms in Cancer

Abstract: Complementary therapies are increasingly used to reduce side effects of cancer treatment, without evidence for their effectiveness. In a randomized, prospective, 2-period, crossover intervention study, the authors tested the effects of therapeutic massage (MT) and healing touch (HT), in comparison to presence alone or standard care, in inducing relaxation and reducing symptoms in 230 subjects. MT and HT lowered blood pressure, respiratory rate (RR), and heart rate (HR). MT lowered anxiety and HT lowered fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
232
2
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(256 citation statements)
references
References 39 publications
9
232
2
13
Order By: Relevance
“…The effectiveness of TT in changing the parameters of vital signs such as blood pressure, heart and respiratory frequency has been verified in cancer patients (8) , critical patients (9) and in healthy individuals (10) . Among the most recent studies addressing TT, a clinical trial was conducted to investigate its effectiveness in improving sleep patterns, among other variables, and the authors found statistically significant results for latency (p=0.000), duration (p=0.008), habitual efficiency (p=0.021), disorders (0.000), daily sleepiness and sleep disorders during the day (0.002) (7) .…”
Section: Physiological Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of TT in changing the parameters of vital signs such as blood pressure, heart and respiratory frequency has been verified in cancer patients (8) , critical patients (9) and in healthy individuals (10) . Among the most recent studies addressing TT, a clinical trial was conducted to investigate its effectiveness in improving sleep patterns, among other variables, and the authors found statistically significant results for latency (p=0.000), duration (p=0.008), habitual efficiency (p=0.021), disorders (0.000), daily sleepiness and sleep disorders during the day (0.002) (7) .…”
Section: Physiological Effectsmentioning
confidence: 99%
“…Even though many studies evaluate the use of TT in isolation, clinical trials have investigated the effectiveness of this strategy in comparison to or in association with other interventions already used in clinical practice, such as: progressive muscle relaxation (6) , massage (8) , cognitivebehavioral therapy (14) , music and guided imagery (15) . In the comparison between TT and progressive muscle relaxation in the reduction of pain and stress in patients with neuropathic pain (6) , the authors found pain improved when TT was implemented (p=0.035), in addition to greater satisfaction with life; the latter showed no statistical significance (p=0.27).…”
Section: Studies Comparing or Associating Tt With Other Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity and duration of massage ranged from one session of 3-45 minutes to 15 sessions over 4 weeks (Jane et al, 2009;Post-White et al, 2003). To be consistent with the research aim to improve physical indicators, the protocol of massage for each participant in the intervention group, one session of massage therapy (for about 60 minutes) was done.…”
Section: Methodsmentioning
confidence: 99%
“…In the University of Minnesota at Minneapolis (17), two hundred thirty patients were randomized to 1 of 3 groups: therapeutic massage (MT), healing touch (HT), or caring presence (P). All subjects received 4 weekly 45-minute sessions of their assigned intervention (MT, HT, or P) and 4 weekly sessions of a standard care/control.…”
Section: The University Of Texas MD Anderson Cancer Center (16)mentioning
confidence: 99%